Komunikasi Politik Pemerintahan Desa dalam Meningkatkan Kinerja Pelayanan Masyarakat Raya Palka Sindangsari - Putri Amelia Simbolon; Julia Ivanna (Journal on Education, 2024)
The results of this research show that effective political communication in Raya Palka Sindangsari Village has succeeded in increasing transparency and accountability in village government, accelerating public services, and increasing community participation and satisfaction. The village government implements various communication strategies such as regular meetings, use of social media and information technology, as well as public awareness campaigns to actively involve the community in decision making. Implementation of budget transparency programs and public consultation forums are examples of initiatives that have succeeded in increasing public trust and participation. However, this research also found several obstacles, such as limited access to technology in several areas and low digital literacy in society. Overall, this research highlights the importance of political communication in creating village government that is effective and responsive to community needs. The recommendations given include increasing access to technology and digital literacy education to support effective political communication in this village.